2021
DOI: 10.30892/gtg.362spl04-686
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Is Too Dangerous! Perceived Risk and the Subjective Safety of Tourism Activity in the Era of Covid-19

Abstract: The COVID-19 pandemic has heightened the risk associated with tourism and induced a paradigm shift in tourist behaviour. The study explores the nexus between COVID-19 induced perceived risk the subjective safety associated with tourism activity. A cross-sectional deductive study was conducted. Data were generated from a respondent-driven snowball sample of 323 potential tourists from all over the world. The key findings indicate perceived physical, psychological and social COVID-19 pandemic induced risk negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Evidently, for venue suppliers, particularly hotels, an opportunity emerged to tap into a new market during COVID-19. Recent literature on the changes in tourism consumption have demonstrated that COVID-19 greatly increased the perceived fear of travelling Wang et al, 2020;Agyeiwaah et al, 2021;Matiza and Slabbert, 2021). The manner in which the virus spreads led to more cautious decision making in travel.…”
Section: Venue-specific Responsesmentioning
confidence: 99%
“…Evidently, for venue suppliers, particularly hotels, an opportunity emerged to tap into a new market during COVID-19. Recent literature on the changes in tourism consumption have demonstrated that COVID-19 greatly increased the perceived fear of travelling Wang et al, 2020;Agyeiwaah et al, 2021;Matiza and Slabbert, 2021). The manner in which the virus spreads led to more cautious decision making in travel.…”
Section: Venue-specific Responsesmentioning
confidence: 99%
“…They also find that these changes had been coupled with larger tourism industry integration, sustainability practices, better housekeeping services, new medical tourism, and virtual tourism among others. On the other hand, Matiza and Stabbet [48] concluded that, in spite of the large number of contemporary studies analyzing the impact of the COVID-19 pandemic on tourism in general, academic work on the effect of the pandemic on the subjective safety associated with tourism activity is still minimal. This could be especially detrimental for islands tourism, because the remoteness and isolation of many islands could create a false sense of their lack of safety.…”
Section: Postpandemic Island Tourism Developmentmentioning
confidence: 99%
“…Nair and Sinha (2020: 307) pinpoint that travel behaviours and specific changes in decision-making are "not new concepts in the tourism industry and have been especially important over the past two decades, as the industry has witnessed a range of catastrophes from natural disasters to terrorist attacks". Yet the COVID-19 is distinctive for the truly global nature of the crisis as the pandemic effectively has halted the operations of the tourism sector in an unparalleled fashion as well as reshaping patterns of consumer travel demand and of supply chains (Buckley, 2020;Hall et al, 2020;Nair and Sinha, 2020;Cooper and Buckley, 2021;Nhamo et al, 2020;Gössling et al, 2021;Matiza and Slabbert, 2021;Pham et al, 2021;Rogerson and Rogerson, 2021a;Sharma et al, 2021;Tellioglu, 2021).…”
Section: Introductionmentioning
confidence: 99%